Diseño y construcción de un simulador de lluvia para el laboratorio de alta tensión de la UPS-Cuenca - Ochoa Cabrera, Juan Diego (2018)
In the present research a sprinkler type rain simulator is designed and built for the high voltage laboratory of the UPS-Cuenca, based on the IEEE std 4 and ANSI 60.1 standards. Built the simulator tests are performed about: BIL, partial discharges and industrial frequency, in a 56-1 pin type insulator within dry and humid environments.